Immediate Effects of Prophylactic Therapeutic Massage on Pain Tolerance and Threshold - Knight, Kyle; Napier, Erin (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Introduction: This study is meant to determine the immediate effects of therapeutic massage on pain tolerance and threshold. Methods: Fourteen subjects were recruited from a sample of convenience. Subjects were randomized to have either the massage or no-massage protocol on their initial visit with the remaining protocol on their following visit. All subjects completed two sessions with the pain-eliciting test, one with the massage protocol and one with the no-massage protocol. Results: All 14 subjects achieved a higher pain tolerance during the massage protocol compared to their own no-massage protocol. The pain tolerance difference between protocols was calculated by a paired T-Test (p value 0.0003) to be a significant difference. No significant difference was found for pain threshold between protocols. Discussion: It appears that therapeutic massage does have a likelihood of increasing pain tolerance when subjects are submitted to a painful stimulus immediately post-massage. This study validates the use of therapeutic massage as an adjunct treatment to improve pain tolerance before a potentially painful procedure. Conclusion: Prophylactic massage was shown to allow healthy participants to achieve a higher pain tolerance when subjected to a pain-eliciting test immediately after the massage was received.